Pathology From Classics to Innovations - Strumfa, Ilze; Bahs, Guntis (IntechOpen, 2021)
Pathology is a diagnostic medical specialty dealing with the evaluation of tissues and body fluids to diagnose disease and predict prognosis or response to treatment. In particular, a biopsy is the "gold standard" in the diagnostics of certain diseases, especially tumours. Pathology - From Classics to Innovations is a collection of original peer-reviewed studies and review articles by a truly global scientific team on the recent advances in pathology. Chapters discuss classic surgical pathology and the application of microscopic tissue studies in anatomic research, immunohistochemistry, molecular pathology, liquid biopsy, and digital pathology.